Effectiveness of a Culturally Adapted Mindfulness-Based Intervention on Blood Pressure, Medication Adherence, and Self-Management: A Quasi-Experimental Study - Ady Irawan.AM; Artini, Kusumaningtyas Siwi; Putri, Anggie Pradana (Journal of Applied Nursing and Health, 2026)
Background: Hypertension is a leading global health problem, with poor adherence to treatment remaining a major barrier to effective control. Mindfulness has emerged as a supportive strategy for improving adherence and self-care. However, the effectiveness in non-Western hypertensive populations remains unclear. This study aimed to evaluate the effectiveness of a culturally adapted mindfulness intervention on blood pressure, medication adherence, and self-care in patients with hypertension in Indonesia. Methods: A nonrandomized quasi-experimental pretest-posttest control group design was employed. 40 adults aged 18-40 years with stage 1 hypertension were recruited through purposive sampling, and the minimum sample size was determined using power analysis (G*Power 3.1), resulting in a minimum of 15 participants per group. To account for attrition, 20 participants were recruited per group. We excluded adults with coronary heart disease, pregnancy, concurrent complementary therapies, or prior mindfulness experience. The study followed the TREND guideline for nonrandomized evaluations. Participants were allocated to an intervention group (n = 20) that received an eight-week culturally adapted mindfulness program delivered in group and individual sessions, or to a control group (n = 20) that received standard care. Data were collected at baseline, post-intervention, and one-month follow-up, using a validated digital sphygmomanometer (blood pressure), the Morisky Medication Adherence Scale-8 (medication adherence), and the Self-Care of Hypertension Inventory (self-care). Ethical clearance was obtained from the institutional review board (No. 109/VII/AUEC/2024), and data were analysed using repeated-measures ANOVA and independent t-tests. Results: Participants in the intervention group experienced significant reductions in systolic and diastolic blood pressure and improved medication adherence compared with the control group, with effects sustained at follow-up (time x group interaction: SBP F = 8.33, p < 0.001, η² = 0.15; DBP F = 7.01, p = 0.002, η² = 0.13; MMAS-8 F = 15.27, p < 0.001, η² = 0.24). Self-care scores increased significantly post-intervention (p = 0.030) but declined at follow-up, with no significant group difference at T2 (p > 0.05). Baseline characteristics were comparable between groups, ensuring equivalence. Conclusion: A culturally adapted mindfulness program effectively improved blood pressure control and medication adherence in Indonesian patients with hypertension, although self-care benefits diminished over time. These findings suggest that mindfulness-based interventions can be a feasible, low-cost complement to standard care, particularly in resource-limited settings. Future studies with larger samples, longer follow-up, and reinforcement strategies are recommended to sustain self-care behaviours.